Profil Penggunaan Obat Antidiabetes Tipe II Di RSUD Dr. Husni Thamrin Natal Medan, Sumatera Utara - Robiatun - Rambe (JURNAL FARMASI DAN MAKANAN, 2022)
The pancreas does not produce enough insulin or the body cannot use the insulin it produces effectively. Insulin is a hormone that regulates the balance of blood sugar levels. (hyperglycemia). This research was conducted with a non-experimental descriptive method with a cross-sectional design that was carried out every month. Sampling was carried out in the internal medicine section of RSUD by Dr. Husni Thamrin Natal. Samples were taken retrospectively every month using secondary data, namely medical records of patients using oral antidiabetics (drugs) in the period from January to June 2019. The data obtained was presented in the form of table proportions and graphs. The results showed that the largest percentage of use of antidiabetic drugs was male, as many as 67 people (57.26%), over 50 years old, as many as 97 people (82.91%), and the type of work was self-employed for as many as 47 people (40, 17%). The most widely used antidiabetic drug groups are the biguanide groups (75.17%), the combination type of drug with a combination of metformin and glimepiride (93.33%), and the frequency of use of the drug metformin (74.15%). Based on the results of the study, it can be concluded that the highest prevalence is in the male sex, and the average age is over 50 years. The pattern of prescribing antidiabetic drugs based on the most widely used drug class is the biguanide group, which is a combination of metformin and glimepiride types of drugs, and the frequency of drug use is metformin.